The epidemiology of multiple sclerosis in the Isle of Man: 2006–2011. (20th April 2015) - Simpson, S.; Mina, S.; Morris, H.; Mahendran, S.; Taylor, B.; Boggild, M.
<x xml:space="preserve">Abstract</x> Background We sought to determine the prevalence of MS on the Isle of Man in 2006 and 2011, and the incidence and mortality rates over this interval. Methods Cases were identified by hospital medical record review, General Practitioners and the local MS Society. The significance of the change in prevalence over time and the significance of differences in frequencies by sex and place of birth were assessed by Poisson regression. Results The 2006 prevalence was 153.64 per 100, 000 persons and the 2011 prevalence was 179.89. The prevalence was higher among females and persons born in the Isle of Man at both time points. The 2006–2011 incidence rate was 6.86 per 100, 000 person‐years, much higher among females and persons born in the Isle of Man. The prevalence sex ratios in 2006 and 2011, 2.77 and 2.59, respectively, and the incidence sex ratio, 2.19, are similar to others found in the region. The mortality rate over the study period was 2.84 per 100, 000 person‐years, this solely among persons born overseas. Conclusions This is the first study of MS epidemiology in the Isle of Man, finding this area to be of high prevalence and to have one of the highest incidence rates in the UK region.